RANCANG BANGUN SISTEM INFORMASI REKAM MEDIS BERBASIS WEB - Santoso, Hari; Sugesti, Sugesti; Gea, Notatema Anugrah (ISTEK WIDURI, 2021)
Medical record is a file that contains records about the patient's identity, examination, treatment, actions and other health services to patients. The speed of obtaining data and processing of data is very much needed in the current technological era. With the development of technology makes people think to be able to work more effectively and efficiently. One of them is making a conventional system into a computerized system. By utilizing website facilities that are connected to the internet, medical records can be more effective and efficient in searching and recording medical history. In this research a web-based information system is designed using the PHP programming language and MySQL database using the waterfall method as its research method. With this system, it is expected to be able to overcome the various needs of users to search for patient data and perform data processing as well as facilitate users in making reports. From the results of research and design that has been implemented to produce medical record applications that facilitate the processing of patient data.